Say Pays! Shareholder Voice and Firm Performance - Vicente Cu\~nat; Mireia Giné; Maria Guadalupe (Institute for the Study of Labor (IZA), 2014)
This paper estimates the effects of Say-on-Pay (SoP); a policy that increases shareholder "voice" by providing shareholders with a regular vote on executive pay. We apply a regression discontinuity design to the votes on shareholder-sponsored SoP proposals. Adopting SoP leads to large increases in market value (4%) and to improvements in long-term performance: profitability and labor productivity increase, while overheads and investment fall. In contrast, we find limited effects on pay levels and structure. This suggests that SoP serves as a regular vote of confidence on the CEO, which leads to higher efficiency and market value.
Keywords: G34; M52; 330; say-on-pay; corporate governance; executive compensation